Appointment letter as a liaison officer for Japanese group at the festival, July 2008 - Shaik Hussain, S. A. (Universiti Malaysia Sarawak, 2008)
Sarawak Tourism Board will organize the 11th Rainforest World Music Festival, a traditional / ethnic musical fiesta from 11-13 July 2008.